Increasing the competitiveness of a vegetal agricultural holding by accesing sub-measure 4.1 - Daniela Nicoleta Bădan; Rozi Liliana Berevoianu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
In this study, is analyzed by elaborating a project using sub-measure 4.1"investment in agricultural holdings" have as their end support for investment to increase competitiveness of agricultural machinery and equipment performance in relation to the current agricultural structure. The actual investment involves purchase you take farming for family business, striving in this way to increase labor productivity, product quality, the use of modern technologies and improvement of working conditions. The varieties grown on 80ha land. are: cereals, leguminous plants, plants producing oilseeds, root vegetables and tubers.In the analysis we estimated two situations: the situation in which grants access EAFRD through Measure 4 sub-measure 4.1 with a public aid for 90 % of the value of the investment and the situation in which one uses a agricultural credit.
Keywords: 330; investment; EAFRD; sub-measure; equipment